Predicted Disease-Specific Immune Infiltration Patterns Decode the Potential Mechanisms of Long Non-Coding RNAs in Primary Sjogren’s Syndrome - Cheng, Caiqi; Zhou, Jun; Chen, Ruiying; Shibata, Yo; Tanaka, Reina; Wang, Jun; Zhang, Jiaming (Frontiers in Immunology, 2021)
Primary Sjogren's syndrome (pSS) is a chronic progressive autoimmune disease with clinical phenotypic "Sicca symptoms". In some cases, the diagnosis of pSS is delayed by 6–7 years due to the inefficient differential diagnosis of pSS and non-SS "Sicca". This study aimed to investigate the difference between these 2 diseases, and in particular, their immunopathogenesis. Based on their gene expression profiles, we systematically defined for the first time the predicted disease-specific immune infiltration pattern of patients with pSS differentiated from normal donors and patients with non-SS "Sicca". We found that it was characterized by the aberrant abundance and interaction of tissue-infiltrated immune cells, such as a notable shift in the subpopulation of 6 immune cells and the perturbed abundance of 9 subpopulations, such as CD4+ memory, CD8+ T-cells, and gamma delta T-cells. In addition, we identified essential genes, particularly long non-coding RNAs (lncRNAs), as the potential mechanisms linked to this predicted pattern reprogramming. Fourteen lncRNAs were identified as the potential regulators associated with the pSS-specific immune infiltration pattern in a synergistic manner, among which the CTA-250D10.23 lncRNA was highly relevant to chemokine signaling pathways. In conclusion, aberrant predicted disease-specific immune infiltration patterns and relevant genes revealed the immunopathogenesis of pSS and provided some clues for the immunotherapy by targeting specific immune cells and genes.